Identifying the organization culture of the UP Diliman library system - Caisip, Edward Bryan C.; Obille, Kathleen Lourdes B. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2018)
In the context of the Philippines, there are only few literature on organizational culture in the library setting. By knowing the organizational culture in the libraries, the managers, particularly the head librarians will be able to use it to their advantage towards the fulfillment of the goals of the libraries. This study identified the organizational culture of the UP Diliman Library System. This was done to contribute to the literature on organizational culture and to guide the library system in the organizational culture that is appropriate for it.
Through a survey questionnaire containing the OCAI and a demographic survey, 131 valid responses were collected to assess and diagnose the organizational culture of the library system. Two (2) interviews were also held between the researcher and the librarian to assess how the difference between the university librarian's and the librarians' perception of the organizational culture. The results of this study identified the organizational culture of the UP Diliman Library System and the differences between the perceptions of the university librarian and the librarians of the library system.
Thesis
Keywords: Organizational behavior; Quality of work life; Leadership